Preclinical evaluation of vascular closure devices - Perkins, Laura E. Leigh; Tu, Merry (Frontiers in Cardiovascular Medicine, 2024)
Vascular closure devices (VCDs) are a diverse class of cardiovascular devices intended to achieve hemostasis following arteriotomy in the common femoral artery for diagnostic and therapeutic interventional procedures. While the preclinical evaluation of VCDs parallel that of many other cardiovascular devices, there are device-specific nuances and model-specific technical considerations in assessing in vivo performance and handling, determining safety, and satisfying regulatory requirements. Despite the multi-decade use and continued development of novel VCD technologies, there is a paucity of published literature on their preclinical evaluation. This review intends to help mitigate this gap through a discussion of conventional animal models, their attributes and limitations, and standards in the in vivo assessment of performance and safety of VCDs.